Legalitas Kewenangan Badan Arbitrase Nasional Indonesia dalam Penerapan Prinsip Competence-Competence - Wiratami, Wiratami (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 4 No 2 (2019)DO - 10.24843/AC.2019.v04.i02.p09, 2019)
According to the doctrine of the principle of competence-competence, the arbitration board has jurisdiction to declare itself whether he has the authority to hear and decide on arbitration disputes. What is meant by the determination of jurisdiction is related to the validity of the arbitration clause and the validity of an agreement. The arbitral tribunal has the authority to evaluate or determine the validity of the arbitration agreement or the validity of the arbitration clause if the parties dispute the matter. The principle of competence-competence is one of the principles regarding the jurisdiction of this arbitration board that has been generally and widely accepted as a principle doctrine in international trade arbitration. This principle is one of the principles regarding the jurisdiction of arbitration board that have been widely accepted and generally as a principle in international commercial arbitration. The legal problems in this research relate to the norm vacancies regarding the competence-competence principle in Law No. 30 of 1999 concerning Arbitration and Alternative Dispute Resolution (hereinafter abbreviated as AAPS Law).Solving research problems using normative legal methods with a legal approach, cases, and analysis of legal concepts. The results of this reseach that (1) The Indonesian National Arbitration Board has been regulated in article 1 point 8 of the Arbitrtion Law and Alternative Dispute Resolution juncto article 31. (2) The provisions of article 18 paragraph 1 of the rules of the Indonesian National Arbitration Board can be used as the legality of authority in determining the validity of the arbitration agreement, if the agreement of the parties “ is not null and void” or is considered to have never existed in its entirety. Menurut doktrin prinsip comptence-competence, arbitrase mempunyai jurisdiksi didalam menyatakan sendiri apakah arbitrase tersebut mempunyai kewenangan untuk mendengarkan dan memutuskan sengketa arbitrase. Penentuan kewenangan arbitrase terkait dengan keabsahan suatu klausul arbitrase maupun perjanjian arbitrase apabila mereka yang membuat perjanjian mempersoalkan mengenai hal itu.Doktrin prinip competence-competence ini merupakan satu dari sekian prinsip mengenai jurisdiksi arbitrase. Doktrin prinsip ini telah dikenal luas sebagai doktrin prinsip dalam arbitrase perdagangan internasional. Permasalahan hukumnya berkaitan dengan adanya kekosongan norma hukum mengenai prinsip competence-competence dalam Undang-Undang Nomor 30 tahun 1999 tentang Arbitrase dan Alternatif Penyelesaian Sengketa (selanjutnya disebut UU AAPS). Penelitian ini menggunakan metode hukum normatif dengan pendekatan perundang-undangan, kasus dan analisa konsep hukum. Hasil dari penelitian ini bahwa (1) BANI telah diatur dalam ketentuan Pasal 1 angka 8 UU AAPS juncto Pasal 31. (2) Ketentuan Pasal 18 ayat (1) Peraturan BANI dapat dijadikan landasan legalitas kewenangan BANI dalam menentukan keabsahan perjanjian arbitarse, apabila perjanjian para pihak untuk menyelesaikan sengketa melalui arbitrase tidak “batal demi hukum” atau dianggap tidak pernah ada secara keseluruhan.